The effect of coconut water on alleviating menstrual pain (dysmenorrhea) in teenage women - Luky Febriani; Elly Wahyuni; Afrina Mizawati (Malahayati International Journal of Nursing and Health Science, 2023)
Background: World Health Organization (WHO) in 2018 stated that the number of dysmenorrhea in the world is very large, on average more than 50% of women in each country experience dysmenorrhea. In the United States, it is estimated that almost 90% of women experience dysmenorrhea and 10-15% of them experience dysmenorrhea severe, which causes them to be unable to carry out any activities. Purpose: To find out "The effect of green coconut water on reducing menstrual pain (dysmenorrhea) in adolescent girls at Junior High School 02 Bengkulu City in 2021.Method: This research was conducted using the method Quasi Experiment with a plan one grup pretest posttest design. Random sampling technique total sampling as many as 28 young women experienced it dysmenorrhea currently. Data analysis consists of univariate, bivariate and multivariate analysis. The sample tests used were Wilcoxon, Mann Whitney and Binary Logistic Regression tests.Results: The results of this study showed that the average pain dysmenorrhea before and after had given coconut water was 5.18 and the average pain after had given coconut water was 2.64. The statistical test results obtained p-value= 0.000, with a mean difference of 2.54 which shows that there is an influence on giving coconut water to young women at Junior High School 02 Bengkulu City in 2021.Conclusion: It is hoped that the school at Junior High School 02 Bengkulu City can optimize School's Health Clinic program services such as increasing the role of officers to implement canteens or school cooperatives to be able to provide coconut water which has the effect of reducing pain dysmenorrhea in teenage girls.